2017
DOI: 10.1097/opx.0000000000001107
|View full text |Cite
|
Sign up to set email alerts
|

Aberrometry Repeatability and Agreement with Autorefraction

Abstract: Significance Commercially-available aberrometers are essential to clinical studies evaluating refractive error and image quality. The Discovery System is a promising clinical instrument that allows investigators to export aberration data for research and analysis purposes. An assessment of the Discovery System’s performance is essential to the interpretation of the data obtained. Purpose To determine the between-visit repeatability of refractive error and higher-order aberration measurements with the Discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
(43 reference statements)
1
15
1
Order By: Relevance
“…However for the cycloplegic group, there was a reduction in the agreement between the astigmatic components (J 0 and J 45 ) measured by QuickSee, those measured by the KR 8800, and SR (Table 4 and Fig 1). These average differences, although noticeable (0.08 D and 0.01 D for J 0 and J 45 , respectively), were smaller than those reported by other authors comparing autorefractors and wavefront aberrometers in young adults under cycloplegic conditions [22,23].…”
Section: Plos Onecontrasting
confidence: 65%
“…However for the cycloplegic group, there was a reduction in the agreement between the astigmatic components (J 0 and J 45 ) measured by QuickSee, those measured by the KR 8800, and SR (Table 4 and Fig 1). These average differences, although noticeable (0.08 D and 0.01 D for J 0 and J 45 , respectively), were smaller than those reported by other authors comparing autorefractors and wavefront aberrometers in young adults under cycloplegic conditions [22,23].…”
Section: Plos Onecontrasting
confidence: 65%
“…However, the quality of the measurement can depend upon a variety of factors, including the availability of the necessary equipment, a suitable environment for testing, the patient’s ability and willingness to cooperate with the examiner, and the examiner’s experience and training. Alternatively, refraction can be measured by using an automated approach, for example, with an automated refractor [11,12], an aberrometer [13], or adaptive optics [14]. Nevertheless, both the subjective and automated techniques require expensive medical equipment and qualified personnel, which can limit their availability and accessibility.…”
Section: Introductionmentioning
confidence: 99%
“…The wavefront measurements in this study were obtained using the Discovery System wavefront sensor. A recent study has shown that the Discovery system is repeatable with no bias between visits and can be used to track changes in higher order aberration 30. However, the study has also implied that the Discovery System cannot be used interchangeably with the COAS wavefront sensor, which is considered the gold standard in the field of wavefront measurement 30.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that the Discovery system is repeatable with no bias between visits and can be used to track changes in higher order aberration 30. However, the study has also implied that the Discovery System cannot be used interchangeably with the COAS wavefront sensor, which is considered the gold standard in the field of wavefront measurement 30. While comparisons between optimized metrics in this study are robust in that all refractions were based upon measurements obtained with the Discovery, comparisons among metric refractions, habitual refraction, and autorefraction may be in question if the Discovery is not in agreement with other instrumentation.…”
Section: Discussionmentioning
confidence: 99%